2021
DOI: 10.31031/tnn.2021.04.000583
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cerebrospinal Fluid Leak at the Clivus: Two Case Reports and Literature Review

Abstract: Spontaneous or non-traumatic cerebrospinal fluid leaks comprise 5-10% of all CSF rhinorrhea. Generally, CSF rhinorrhea occur at Cribriform plate, sella, sphenoid sinus and ethmoid air. Primary CSF rhinorrhea from clival defect is extremely rare. We herein describe two cases of spontaneous CSF rhinorrhea through the clivus repaired with endoscopic endonasal trans sphenoid approach. Moreover, we collected evidence in the literature regarding potential etiology, symptom and treatment (which occurred in the case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For skull base reconstructions due to spontaneous CSF leakage at the clivus, previous studies have reported harvesting autografts and conducting a multilayered reconstruction (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, these techniques require invasive procedures outside the main surgical site, i.e., the endonasal area, to harvest the reconstructive material.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For skull base reconstructions due to spontaneous CSF leakage at the clivus, previous studies have reported harvesting autografts and conducting a multilayered reconstruction (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, these techniques require invasive procedures outside the main surgical site, i.e., the endonasal area, to harvest the reconstructive material.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous cerebrospinal fluid (CSF) leakage is relatively rare, accounting for approximately 5-10% of all types of CSF leaks [ 1 ]. Such leaks at the clivus are particularly rare [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations